The religion and rituals of the nomads of pre-Islamic Arabia : a reconstruction based on the Safaitic inscriptions - Al-Jallad, Ahmad (Ancient Languages and Civilizations, 2022)
"This book approaches the religion and rituals of the pre-Islamic Arabian nomads using the Safaitic inscriptions. Unlike Islamic-period literary sources, this material was produced by practitioners of traditional Arabian religion; the inscriptions are eyewitnesses to the religious life of Arabian nomads prior to the spread of Judaism and Christianity across Arabia. The author attempts to reconstruct this world using the original words of its inhabitants, interpreted through comparative philology, pre-Islamic and Islamic-period literary sources, and the archaeological context"--